Implementasi Penetapan Nilai Jual Objek Pajak pada Pendapatan Asli Daerah di Kabupaten Banjar Provinsi Kalimantan Selatan - Ahmad Yunani (Ecoplan, 2022)
The determination of the NJOP is based on the assessment of the land and property/buildings carried out by the Regional Government. The purpose of this research is to find out how to determine the selling value of tax objects and their implications for land and building tax revenues in Banjar Regency. The method in this research is descriptive. This research was conducted in the working area of Kertak Hanyar and Gambut Districts. The data collection technique used in this research is a field study. The data analysis method used in this research is descriptive quantitative data analysis. The results of this study are that Banjar Regency determines the selling value of the tax object of each taxpayer differently according to the location and condition of the tax object, namely land and buildings. Such as the determination of NJOP in Kertak Hanyar and Gambut Districts, where these two sub-districts are one of the largest contributors to income sourced from PBB Taxes because they are developed sub-districts which are dominated by housing, trade, services, and industry activities. There is a lot of land conversion from agricultural land to other land functions such as housing, business, industry, and services. The determination of land and building NJOP is still an NJOP determination adopted from KPP Pratama since the transfer of Land and Building Tax for Rural and Urban sectors from central tax to local tax on January 1, 2014, until now. UN revenues that have the highest potential are in Kertak Hanyar and Gambut Districts. Local governments must assess and reprocess data, especially between the selling value of tax objects (NJOP) and selling prices that occur in the community, and update PBB objects from previous data, such as non-taxable tax objects (public facilities) so that the determination of NJOP become more relevant. Local governments need to re-establish NJOP for data that has not been subject to PBB, or updating existing data will increase the selling value of tax objects that are the basis for imposing PBB.